Academic Socialization Among Latino Families: Exploring the Compensatory Role of Cultural Processes. Issue 3 (2nd July 2016) - Rivas-Drake, Deborah; Marchand, Aixa
Abstract : This study examines the relation of parent educational expectations, cultural socialization, and familism with academic adjustment among 150 Latino parent–adolescent dyads (81% Mexican origin; 79% were mothers). Adolescents (53% girls) responded to measures of school engagement, educational utility, parental educational expectations, cultural socialization, and familism. Results suggest that, after accounting for parents' reported educational attainment, adolescents' perceptions of academic and cultural socialization messages and their own endorsement of familism were uniquely related to school engagement; only parental educational expectations were uniquely related to beliefs about the utility of education. Cultural and academic socialization may thus complement each other.